A Note on the Indian Planetary Exaltations and their Greek-Language Sources - Gansten, Martin (History of Science in South Asia, 2020)
A close examination of the lists of planetary exaltations given by two of the earliest known Sanskrit authors on horoscopic astrology – Mīnarāja and Sphujidhvaja – solves the confusion surrounding Mīnarāja’s idiosyncratic assignment of degrees and suggests that both authors, and indeed all later Indian astrological literature, depended for this doctrine on a single, Greek-language source.